Anti‐Sclerostin Antibody Treatment in a Rat Model of Progressive Renal Osteodystrophy. (March 2015) - Moe, Sharon M; Chen, Neal X; Newman, Christopher L; Organ, Jason M; Kneissel, Michaela; Kramer, Ina; Gattone, Vincent H; Allen, Matthew R
ABSTRACT Chronic kidney disease (CKD) is associated with abnormalities in bone quantity and quality, leading to increased fractures. Recent studies suggest abnormalities of Wnt signaling in animal models of CKD and elevated sclerostin levels in patients with CKD. The goal of this study was to evaluate the effectiveness of anti‐sclerostin antibody treatment in an animal model of progressive CKD with low and high parathyroid hormone (PTH) levels. Cy/+ male rats (CKD) were treated without or with calcium in the drinking water at 25 weeks of age to stratify the animals into high PTH and low PTH groups, respectively, by 30 weeks. Animals were then treated with anti‐sclerostin antibody at 100 mg/kg i.v. weekly for 5 doses, a single 20‐µg/kg subcutaneous dose of zoledronic acid, or no treatment, and were then euthanized at 35 weeks. As a positive control, the efficacy of anti‐sclerostin antibody treatment was also evaluated in normal littermates. The results demonstrated that the CKD animals with high PTH had lower calcium, higher phosphorus, and lower FGF23 compared to the CKD animals with low PTH. Treatment with anti‐sclerostin antibody had no effect on any of the biochemistries, whereas zoledronic acid lowered dkk‐1 levels. The anti‐sclerostin antibody increased trabecular bone volume/total volume (BV/TV) and trabecular mineralization surface in animals with low PTH, but not in animals with high PTH. Neither anti‐sclerostin antibody nor zoledronic acid improved biomechanical properties in the animals. Cortical porosity was severe in high‐PTH animals and was unaffected by either treatment. In contrast, in normal animals treated with anti‐sclerostin antibody, there was an improvement in bone volume, cortical geometry, and biomechanical properties. In summary, this is the first study to test the efficacy of anti‐sclerostin antibody treatment on animals with advanced CKD. We found efficacy in improving bone properties only when the PTH levels were low. © 2014 American Society for Bone and Mineral Research